Ageing Population in Nepal: Challenges and Management - Yadav, Raj Kumar (Academic Voices: A Multidisciplinary Journal, 2013)
Ageing is not yet understood as a demographic as well as socio-economic problem in Nepal with adequate reflection in the policy and plan documents. However, gradual decline in fertility, rapidly increasing technological diffusion along with considerable control in mortality increasing ageing have challenged it’s properly management. Internal conflicts, poor socio-economic and inadequate resource base of the country have difficulties in coping with the problems of aging espoused with unemployment among adults. Transitions in social status, economic motive and family attitude, norms and values and transformation from joint to nuclear family structure have also challenged its properly rearing and caring. Coherent and aggressive policy and programmed measures are required to combat the issues of elderly as well as welfare for all in Nepal Academic Voices, Vol. 2, No. 1, 2012, Pages 48-53 DOI: http://dx.doi.org/10.3126/av.v2i1.8287